Modelling an off-grid integrated renewable energy system for rural electrification in India using photovoltaics and anaerobic digestion - Castellanos, J.G.; Walker, M.; Poggio, D.; Pourkashanian, M.; Nimmo, W. (Renewable Energy, 2015)
This work describes the design optimisation and techno-economic analysis of an off-grid Integrated Renewable Energy System (IRES) designed to meet the electrical demand of a rural village location in West Bengal – India with an overall electrical requirement equivalent to 22 MWh year−1. The investigation involved the modelling of seven scenarios, each containing a different combination of electricity generation (anaerobic digestion with biogas combined heat and power (CHP) and photovoltaics) and storage elements (Vanadium redox batteries, water electrolyser and hydrogen storage with fuel cell). Micro-grid modelling software HOMER, was combined with additional modelling of anaerobic digestion, to scale each component in each scenario considering the systems' ability to give a good quality electricity supply to a rural community. The integrated system which contained all of the possible elements – except hydrogen production and storage presented the lowest capital ($US 71 k) and energy cost ($US 0.289 kWh−1) compared to the scenarios with a single energy source. The biogas CHP was able to meet the electrical load peaks and variations and produced 61% of the total electricity in the optimised system, while the photovoltaics met the daytime load and allowed the charging of the battery which was subsequently used to meet base load at night.
Keywords: Integrated renewable energy system; Micro-grid; Photovoltaic; Anaerobic digestion; Hydrogen fuel cell; Rural electrification